The Effect of Therapeutic Whirlpool and Hot Packs on Hand Volume During Rehabilitation After Distal Radius Fracture: A Blinded Randomized Controlled Trial. (May 2017) - Szekeres, Mike; MacDermid, Joy C.; Birmingham, Trevor; Grewal, Ruby; Lalone, Emily
Background: Edema is a possibility with all heating modalities due to the increase in local blood flow caused by vasodilation. Despite the frequent application of superficial heat modalities, their relative effect on hand volume has not been determined for the upper extremity. The objective of this study was to compare the immediate effects of hot packs and whirlpool on hand volume for patients with distal radius fracture (DRF) and to determine whether any changes in volume between these modalities were still present 30 minutes after heat application. Finally, to determine whether there were any differences in volume change between groups after 3 repeated therapy visits.Methods: Sixty patients with clinically healed DRFs were divided into 2 groups. Half received therapeutic whirlpool at each therapy visit, and the other half received a moist hot pack treatment for 3 consecutive visits. Hand volume was measured before heat, after heat, and at the end of each 30-minute therapy session.Results: There was a significant difference between groups immediately after heat application, as patients in the whirlpool group experienced an initial volume increase greater than those who received a hot pack. When remeasured after a hand therapy session approximately 30 minutes later, this group difference in volume change was no longer significant. The overall change in volume from enrollment in the study to completion of the study 3 weeks later was not statistically different between groups.Conclusion: Whirlpool is a potential consideration when selecting a heat modality for patients with DRF.